Foreign investment as the beginning of the presence of westernization of American culture in Indonesia - Hari Naredi; Melinda Rahmawati (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2022)
Since 1967, foreign investment in Indonesia has led to the westernization of American culture among Indonesians. Westernization is a challenge for Indonesian people in terms of preserving their own culture. This study aimed to determine the impact of foreign investment as the beginning of the spread of the westernization of American culture in Indonesia. This study utilized descriptive qualitative methods with an analysis of literature studies that specifically discussed the impact of foreign investment as the beginning of the westernization of American culture in Indonesia. The results of this study indicate that the westernization of American culture occurs because of foreign investment in Indonesia so that Indonesian people adopt some of the culture brought by that country. This study finds that the cultural shift in Indonesian society is caused by the westernization of American culture among the people. This westernization is the result of Indonesia’s opening to foreign investment, which has brought their culture to Indonesia. As a result, cultural assimilation occurs, leading to a cultural shift through westernization, especially in urban communities.